DESIGN OF A SHARED CONTROL INTERFACE FOR A POWERED WHEELCHAIR - Malik, Asset (School of Engineering and Digital Sciences, 2023)
Powered wheelchairs significantly improve mobility of individuals with physical limitations, but their high cost and challenges associated with traditional joystick controls often limit their accessibility and ease of use. This thesis aims to explore alternative modern input methods for controlling a standard powered wheelchair aiming to redesing the system for shared control implementation. A ground-up approach is taken, covering wheelchair electronics modification, localization, path planning, and comparison of different input methods. The research primarily focuses on the development and evaluation of a experimental prototype based on an Otronica Pulse 310 electric wheelchair with a ZED2 camera and ROS installed laptop. Localization performance was optimized using Simultaneous Localization and Mapping (SLAM) by combining the ZED2 camera with encoders. Caster wheel-aware path planning was achieved using Model Predictive Control (MPC) and potentiometers mounted directly on the axis. Various user input methods, such as touchscreen control and shared control, were investigated, which proved to be more comfortable and user-friendly than traditional joystick controls. Despite the limited time available for implementation, the study provides a solid foundation for future research on wheelchair input methods, path-planning, and control systems. It also offers valuable insights for enhancing the lives of powered wheelchair users through improved control interfaces, shared control, and navigation technologies.
Keywords: type of access: open access; Powered Wheelchair